Role of golimumab for the treatment of rheumatoid arthritis. (June 2014) - Tran, Gui; Emery, Paul
Golimumab, a fully humanized anti-TNFα monoclonal antibody, is a recent addition to this class of biological agents used in the treatment of rheumatoid arthritis (RA). Phase II and III trials have shown that subcutaneous and intravenous administration of golimumab alongside methotrexate is both efficacious and well tolerated in treating RA. As with other TNF inhibitors, studies have shown no increased risk of death or malignancy with its use, although there is potentially an increased risk of serious infection. Golimumab is a safe and effective treatment in RA and, uniquely within this class, has been shown to be effective in patients who have failed previous anti-TNFα treatment.